2012
DOI: 10.1007/s13238-012-2067-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of p53 and MDM2 polymorphisms on susceptibility and surgical prognosis in hepatitis B virus-related hepatocellular carcinoma

Abstract: The p53 signaling pathway works as a potent barrier to tumor progression. Two single nucleotide polymorphisms (SNPs) in the gene loci of p53 pathway, p53 codon 72 Arg72Pro and MDM2 SNP309 (T > G), have been shown to cause perturbation of p53 function, but the effect of the two SNPs on the risk of hepatocellular carcinoma (HCC) remains inconsistent. This study investigated the influence of combined p53 Arg72Pro and MDM2 SNP309 on the risk of developing HCC in patients with chronic hepatitis B virus infection, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Concerning the association between SNP309 and prognostic factors related to HCC after surgical treatment, current literature is scarce. A single study conducted by Yang et al in 2003 (26) contemplated this association and noticed patients presenting G/G genotype had disease-free survival and global survival similar to other genotypes.…”
Section: Discussionmentioning
confidence: 98%
“…Concerning the association between SNP309 and prognostic factors related to HCC after surgical treatment, current literature is scarce. A single study conducted by Yang et al in 2003 (26) contemplated this association and noticed patients presenting G/G genotype had disease-free survival and global survival similar to other genotypes.…”
Section: Discussionmentioning
confidence: 98%
“…p53 is one of the most studied proteins that plays fundamental role in regulating basic cellular function and because of this, it is an important target protein to study different polymorphic variants of p53 for their association with various diseases including colon carcinomas [10,[12][13][14]27]. A SNP in MDM2 (SNPT309G), a negative regulator of p53, alone or in combination with p53 has been reported to associate with different carcinomas and progression of disease [14,18,22,23,25,[27][28][29][30]. Over the last decade, studies have reported the role of p53 R72P and MDM2 T309G polymorphisms as risk factor for colorectal carcinoma [14,15,19,[23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the T to G polymorphism in MDM2 SNP309 on cancer prognosis has been investigated in several studies in recent years where the G allele in MDM2 SNP309 is found to significantly correlate with long‐term survival in pancreatic cancer , chronic lymphocytic leukemia and possible hepatocellular carcinoma among others . That other studies found a correlation between MDM2 SNP309 polymorphism and long‐term survival strengthen our findings that there may be a plausible impact of the MDM2 SNP309 polymorphism on DLBCL prognosis for some patients.…”
Section: Discussionmentioning
confidence: 99%